Knowledge, attitude, and practices of complementary and alternative medicine: a survey of physicians and nurses at an academic medical center in Beirut. Issue 1 (31st December 2022) - Makarem, Nisrine N.; Brome, Dayana; Romani, Maya
ABSTRACT: The aim of this study is to assess the knowledge, attitudes, and practices of complementary and alternative medicine (CAM) among physicians and nurses at the American University of Beirut Medical Center (AUBMC) in Beirut, Lebanon. A web-based survey was emailed to 518 physicians and 423 registered nurses in all medical departments at AUBMC. Of the 94 physicians responding to the survey, 61% have never referred a patient to a CAM practitioner yet 33% reported that they would refer if available. Sixty-two percent of physicians believed that incorporating evidence-based CAM therapies will increase patient satisfaction and 66% thought that offering CAM would attract more patients. Of the 80 nurses who responded, 78.7% have never referred a patient to a CAM practitioner, yet half reported that they would likely refer if a CAM practitioner was available. Fifty-seven percent of nurses surveyed believed that offering CAM would attract more patients while 59% thought that it would increase patient satisfaction. Most nurses were uncomfortable counseling patients about CAM modalities. Favorable attitudes towards CAM were reflected by the physicians and nurses as signified by the above-average attitude means towards CAM (M = 4.01, SD = .16 and M = 3.25, SD = .59, respectively). The study findings demonstrate that despite the physicians' and nurses' limited knowledge and their discomfort in counseling on CAM, they expressed acceptability and willingness in using and incorporating CAM therapies into clinical practice at AUBMC. This is the first study conducted in Lebanon that assesses both nurses' and physicians' perspectives on the use of all CAM domains in general within the same healthcare setting. This study not only provides baseline data but also highlights the knowledge gap and learning needs among physicians and nurses with regards to CAM.